The Association Between Diabetes Mellitus and Atrial Fibrillation: Clinical and Mechanistic Insights - Bohne, Loryn J.; Johnson, Dustin; Rose, Robert A.; Wilton, Stephen B.; Gillis, Anne M. (Frontiers in Physiology, 2019)
A number of clinical studies have reported that diabetes mellitus (DM) is an independent risk factor for AF. After adjustment for other known risk factors including age, sex and cardiovascular risk factors, DM remains a significant if modest risk factor for development of AF. The mechanisms underlying the increased susceptibility to AF in DM are incompletely understood, but are thought to involve both electrical and structural remodeling in the atria. Electrical remodeling in DM may involve alterations in gap junction function that affect atrial conduction velocity due to changes in expression or localization of connexins. Electrical remodeling can also occur due to changes in atrial action potential morphology in association with changes in ionic currents, such as sodium or potassium currents, that can affect conduction velocity or susceptibility to triggered activity. Structural remodeling in DM results in atrial fibrosis, which can alter conduction patterns and susceptibility to re-entry in the atria. In addition, increases in atrial adipose tissue, especially in Type II DM, can lead to disruptions in atrial conduction velocity or conduction patterns that may affect arrhythmogenesis. Whether the insulin resistance in type II DM activates unique intracellular signaling pathways independent of obesity requires further investigation. In addition, the relationship between incident AF and glycemic control requires further study.